ANTZERKIA - Aresti, Gabriel; Labayen, Antonio Mª (EGAN, 2021)
GABRIEL ARESTI: MUGALDEKO HERRIAN EGINIKAKO TOBERA ANTONIO Mª LABAYEN: GALTZAUNDI EUSEBIO ERKIAGA-K IRABAZI DU DOMINGO AGIRRE NOVELA-SARIA GABRIEL ARESTI-K IRABAZI DU 1961 TORIBIO ALZAGA TEATRO-SARIA